Baby dinosaur - Sirett, Dawn; Minister, Peter (London Dorling Kindersley, 2018)
From bumpy scales to tough, pointy horns, there are all sorts of dinosaur textures for baby to explore in this sturdy book
Picture
1 2 13
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs; Picture book for children